HUBUNGAN ANTARA IKLIM KOMUNIKASI ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN PT. PARAMOUNT ENTERPRISE INTERNATIONAL - Hafiar, Hanny; Lukman, Syauqy; Marvian, Ananda (Jurnal Nomosleca, 2018)
Abstract The aim of this study is to acknowledge the correlation between organizational communication climate and job satisfaction in PT. Paramount Enterprise International. This study used Human Relation theory abd correlation method with descriptive and inferential statistical analysis. The amount of samples was 52 people which was obtained by simple random sampling technique. The data was obtained by questionnaire, interview, and literature review. The result of this study was that there was strong correlation between organizational communication climate and job satisfaction. The conclusion of this study was that there was strong relationship between trust, making a decision together, honesty, listening to the upward communication, attention to high-performance goals with job satisfaction aspects, and a significant relationship between openness to downward communication and the job satisfaction aspects. Based on these conclusions, the researcher suggests increasing the time intensity of listening to employees and telling them frankly also promising to find and develop a communication plan if the leader does not have the information which the employee needs. Keyword: Human Relation Theory, Organisational Communication Climate, Job Satisfaction.DOI :Â https://doi.org/10.26905/nomosleca.v4i2.2543